THE INNOVATIVE MECHANISM OF DEVELOPMENT OF ECONOMY OF THE EUROPEAN UNION IN THE CONDITIONS OF THE INTERNATIONAL MOVEMENT OF PRODUCTION FACTORS - E. Smirnov; V. Kirillov (Вестник университета, 2016)
In the present article problems of improvement of the innovative mechanism of development of the European Union’s economy on the basis of strengthening of its participation in the international movement of factors of production are analyzed. The role of the international movement of the capital, migration of labor and scientific and technical cooperation in development of supranational innovative system of the region is shown.